A Comprehensive Review on Eclipta alba (L.) Hassk.: Phytochemistry, Pharmacology, and Therapeutic Potential - Yanadaiah J. P., (Asian Journal of Pharmaceutics (AJP), 2025)
Eclipta alba (L.) Hassk., widely referred to as Bhringraj, is a well-documented herb traditionally used in various traditional healing systems such as Ayurveda, Unani, Siddha, and Traditional Chinese medicine. Belonging to the Asteraceae family, this plant is distributed all over the world. It has been used ethnomedicinally to treat liver disorders, skin infections, respiratory ailments, and promote hair growth. In recent years, E. alba has garnered increasing scientific attention due to its diverse pharmacological actions and the presence of a rich spectrum of bioactive phytoconstituents. This review comprehensively compiles existing knowledge on the botanical characteristics, traditional uses, phytochemistry, and pharmacological activities of E. alba. It highlights key constituents such as wedelolactone, eclalbasaponins, apigenin, luteolin, and stigmasterol, which have shown potential in antioxidant, hepatoprotective, anti-inflammatory, antimicrobial, neuroprotective, and anticancer models. The review further discusses recent developments, clinical investigations, and applications of E. alba in dermatology and neurodegenerative conditions. In addition, the article emphasizes gaps in clinical validation, dosage standardization, and toxicity profiling that need to be addressed to enhance its integration into evidence-based medicine. Overall, this review reaffirms E. alba as a promising herb with considerable therapeutic potential and encourages continued pharmacological and phytochemical exploration.